A comparison of buccal versus vaginal misoprostol administration for induction of first and second trimester abortion - Yadav, Amita; Kaushal, Nikita; Sonkar, Shubhangi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Aim of study was to compare effectiveness, adverse effects and patient’s acceptability of buccal and vaginal routes of administration of misoprostol in 1st and 2nd trimester abortion, type of study-randomized control trial Methods: A total of 200 women with indications for abortion up to 20 weeks of pregnancy were enrolled over a period of 1 year and received misoprostol either through buccal (Group A) or vaginal (Group B) route. Each group containing 50 patients of first trimester and second trimester. Results: Incomplete abortion rate (25%) was significantly higher in vaginal group while drug related side-effects (47%), patients’ satisfaction and acceptability (82%) was higher in buccal group respectively. Conclusions: Buccal route may be preferred owing to a better complete abortion rate, better patient satisfaction and acceptability as compared to vaginal route.